Age and Gender Profiling in the Chinese and Mexican Labor Markets: Evidence from Four Job Boards - Miguel Delgado Helleseter; Peter J. Kuhn; Kailing Shen (Institute for the Study of Labor (IZA), 2016)
When permitted by law, employers sometimes state the preferred age and sex of their employees in job ads. We study this practice using data from one Mexican and three Chinese job boards, showing that it is widely used to request both genders and is especially prevalent in jobs with low skill requirements. For example, on the job board serving less-skilled production and service workers in China, 72 percent of ads specified a preferred gender, and 77 percent listed both a minimum and maximum age. We also document a new stylized fact we call the age twist in gender profiling: firms' explicit gender requests shift dramatically away from women and towards men when firms are seeking older (as opposed to younger) workers. While some of this twist can be attributed to employers' age-dependent requests for (female) beauty and (male) leadership, the timing of the shift suggests that young women's movement into childbearing also plays a role.
Keywords: J16; J63; J71; 330; gender; discrimination; age; China; Mexico; Internet; beauty; search; recruiting; screening